COOPERATION BETWEEN LOCAL AUTHORITIES AND RELIGIOUS ACTORS AS A KEY FACTOR IN PREVENTING CONFLICT. THE CASE OF HINDU AND SIKH COMMUNITIES IN THE ITALIAN CITIES OF NOVELLARA AND REGGIO EMILIA (Religious dialogue and cooperation, 2023)
Religious actors are often called to take an active part in initiatives promotedby European Institutions because of their potential to prevent conflict and ease socialtensions that can arise among people of different religions. Member States are called tosupport a sustained, open and transparent dialogue with the different religions communitiesas a tool for peacekeeping and promoting social cohesion in Europe and at its borders.The role of local authorities is crucial in this process; virtuous cases are the Italianmunicipalities of Novellara and Reggio Emilia, whose abilities to value the presence ofSikh and Hindu communities in their territories led to the publication of a Handbook forLocal Authorities, titled “Valuing religious communities as key actors of social cohesion”,with the patronage of the Council of Europe: an example of how local best practices caninfluence European principles from the bottom up. The paper aims to explore in detail thedifferent ways in which these religious actors and local governments collaborate and cooperate:the enhancement of places of worship, the promotion of interfaith dialogue andthe shared participation in religious festivities. These are policy strategies aimed towardsa collective education for plural and inclusive citizenship.
Keywords: Religious actors; Local Authorities; Hindus; Sikhs; Interreligious dialogue